Carbon ceramic brake disc and preparation method thereof

By using plain wrist fabric and tire mesh structure in the manufacturing process of carbon ceramic brake discs, combined with the modification technology of porous molybdenum disulfide-hydroxymagnesium silicate composite and phenolic resin, the shortcomings of existing carbon ceramic brake discs in terms of wear resistance and strength are solved, and a higher service life and lower maintenance costs are achieved.

CN119638465AActive Publication Date: 2025-03-18SHENZHEN LE MYTH TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411799124.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-18
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The existing carbon ceramic brake discs face problems such as material uniformity, molding difficulty and high cost during the manufacturing process, and their wear resistance and strength are insufficient, making it difficult to meet the needs of high strength and long-term use.

Method used

Plain wrist fabrics are used instead of weftless fabrics to increase structural strength and use tire mesh in the friction layer to improve ceramic content and wear performance. At the same time, a porous molybdenum disulfide-hydroxymagnesium silicate composite was prepared and loaded with iron tetroxide on it to improve the strength and wear resistance of the brake disc. Diethylene triamine modified phenolic resin is used to improve the dispersion properties of the composite.

Benefits of technology

It significantly improves the wear resistance and strength of the carbon ceramic brake disc, extends the service life, improves working stability, reduces maintenance costs, and enhances the safety and reliability of the brake system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a carbon-ceramic brake disc and a preparation method thereof, and relates to the technical field of carbon-ceramic brake discs. Plain cloth is used for replacing non-woven cloth, the strength of a structural part is improved, on the other hand, a friction layer adopts a tire net, the defect that the non-woven cloth on a friction surface is prone to falling off is overcome, the fiber content of the tire net is greatly reduced, and the friction surface is protected. Hydroxyl magnesium silicate with excellent wear resistance is prepared, then hydroxyl magnesium silicate and porous molybdenum disulfide are compounded, and ferroferric oxide is loaded on a porous molybdenum disulfide-hydroxyl magnesium silicate compound by adding ferric trichloride and ferric chloride tetrahydrate, so that the wear resistance of the material is improved, and the wear resistance of the material is improved. And the strength and wear resistance of the carbon-ceramic brake disc are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon-ceramic brake discs, in particular to a carbon-ceramic brake disc and a preparation method thereof. Background Art

[0002] In modern high-performance vehicles, especially in the fields of racing, military and aviation, the requirements for brake systems are getting higher and higher. As an important component of the brake system, the wear resistance, strength and thermal stability of the brake disc will directly affect the safety and reliability of the brake. Traditional cast iron brake discs have gradually failed to meet the needs of high-intensity and long-term use due to their poor wear resistance. In recent years, carbon-ceramic composites, as a new type of brake disc material, have been widely used in high-end fields such as aviation and racing due to their high strength, high temperature resistance, thermal decay resistance and low thermal expansion coefficient.

[0003] However, carbon ceramic brake discs still face many challenges in the manufacturing process, including material uniformity, molding difficulty, and high cost. In particular, how to improve its wear resistance and strength and further enhance braking performance is still a difficult point in technical research and development. Therefore, the development of a new type of wear-resistant, high-strength carbon ceramic brake disc and its preparation method has become an urgent need for the development of industry technology. This can not only improve the service life and working stability of the brake disc, but also reduce the maintenance cost of the vehicle and enhance the safety and reliability of the brake system.

[0004] In summary, in order to solve the above problems, the present invention provides a carbon-ceramic brake disc and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide a carbon-ceramic brake disc and a preparation method thereof to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a carbon-ceramic brake disc comprises the following steps: Step 1: Take phenolic resin B, silicon powder, ceramic powder, porous molybdenum disulfide-hydroxy magnesium silicate composite, adjust the pH value to 11-12, and ball mill for 46-48 hours to obtain a mixed slurry; Step 2: stacking the plain cloth and the tire net in a circular manner to obtain an intermediate layer; then laying the tire net flat on the upper and lower surfaces of the intermediate layer, and needle punching to obtain a fiber preform; Step 3: Immerse the fiber preform in the mixed slurry for 10-15 minutes, take it out, dry it, keep it warm for 30-40 minutes at 150℃ and 30MPa, thermally crack it at 1000-1100℃, keep it warm at 1800℃ for 50-60 minutes, process it into the shape of a brake disc, and then siliconize it in a vacuum furnace, keep it warm, introduce nitrogen to 0.1MPa at 1300-1600℃, cool it, and grind it to obtain a carbon ceramic brake disc.

[0007] More optimally, the preparation method of the porous molybdenum disulfide-hydroxymagnesium silicate complex is: take porous molybdenum disulfide, hydroxymagnesium silicate, and sodium alginate solution, ultrasonically disperse to obtain a mixed solution A; take ferric chloride, ferric chloride tetrahydrate, and deionized water, stir evenly, drop into the mixed solution A, heat to 60-65°C, react for 40-50 minutes, freeze-dry, and grind to obtain a porous molybdenum disulfide-hydroxymagnesium silicate complex.

[0008] More optimally, the preparation method of the porous molybdenum disulfide is: take ammonium heptamolybdate, thiourea, and deionized water, ultrasonically treat for 5-10 minutes, react at 195-200°C for 22-24 hours, cool, wash, and dry to obtain porous molybdenum disulfide.

[0009] More optimally, the preparation method of the magnesium hydroxysilicate is: take magnesium oxide, silicon dioxide, and distilled water, stir evenly, add sodium hydroxide solution, heat to 200°C and react for 10-12h, cool to 25-30°C, wash, dry, grind, and ball-mill to obtain magnesium hydroxysilicate.

[0010] More optimally, the preparation method of the phenolic resin B is: take phenolic resin A, ethanol, acetone, and hexamethylenetetramine, mix them evenly, and obtain phenolic resin B.

[0011] More optimally, the preparation method of the phenolic resin A is: take ammonia water, deionized water, and ethanol, stir for 60-70 minutes, add resorcinol and diethylenetriamine, stir for 30-40 minutes, add formaldehyde solution dropwise, continue stirring for 22-24 hours, centrifuge, wash, and dry to obtain phenolic resin A.

[0012] More optimally, the mass ratio of the phenolic resin A, ethanol, acetone and hexamethylenetetramine is 1:1:1:0.1.

[0013] More preferably, the ceramic powder is SiC, B 4 C, BN; the particle size of the ceramic powder is 0.5-5 μm.

[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses plain cloth instead of non-woven cloth to increase the strength of the structure. On the other hand, the friction layer adopts a tire mesh to solve the defect that the non-woven cloth on the friction surface is easy to fall off. The fiber content of the tire mesh is greatly reduced, and the ceramic content of the friction surface is increased, thereby improving the wear performance of the material. The fiber distribution of the tire mesh structure is uniform, which improves the stability of the friction coefficient of the material.

[0015] The present invention adds a process of introducing nitrogen to 0.1 MPa at 1300-1600° C., and generates silicon nitride through the reaction of nitrogen and silicon. By utilizing the non-wetting property of silicon nitride and silicon, silicon slag on the surface of the brake disc can be effectively reduced, thereby improving the product qualification rate.

[0016] Add silicon powder. The silicon powder can first form a SiC barrier layer with resin carbon, slowing down the reaction speed of subsequent siliconizing treatment, making the brake disc siliconized more uniformly and improving the product qualification rate.

[0017] 2. The present invention prepares a hydroxy magnesium silicate with excellent wear resistance, and then composites the hydroxy magnesium silicate with porous molybdenum disulfide. By adding ferric chloride and ferric chloride tetrahydrate, the porous molybdenum disulfide-hydroxy magnesium silicate composite is loaded with ferrosinite, thereby further improving the strength and wear resistance of the carbon ceramic brake disc.

[0018] 3. The present invention uses diethylenetriamine to prepare a phenolic resin B. The addition of diethylenetriamine improves the chelating property between the phenolic resin B and the porous molybdenum disulfide-hydroxymagnesium silicate composite, thereby improving the dispersion performance of the porous molybdenum disulfide-hydroxymagnesium silicate composite and improving the strength and wear resistance of the carbon-ceramic brake disc. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The models and manufacturers of the substances involved in the present invention are not particularly limited, and illustratively include: plain cloth: polyester-cotton plain cloth, item number: XT-A-04; can be purchased from Jinzhou Xinteng Textile Distribution Office; tire net: needle-punched net tire preform, item number: WT-YZT-1; can be purchased from Jiaxing Naco New Materials Co., Ltd.; magnesium oxide: particle size 40nm, can be purchased from Shuitian Material Technology Co., Ltd.; silicon dioxide: particle size 40nm, can be purchased from Shuitian Material Technology Co., Ltd.; silicon powder: 0.3um, can be purchased from Jiangsu Huimai Powder Technology Co., Ltd.

[0021] Embodiment 1: A method for preparing a carbon ceramic brake disc, comprising the following steps: Step 1: Preparation of fiber preform: The plain cloth and the tire net are stacked in a cycle to obtain an intermediate layer; then the tire net with a thickness of 5 mm is laid flat on the upper and lower surfaces of the intermediate layer, and needle punching is performed to obtain a fiber preform; the needle punching density is 10 needles / cm 2 The volume density of the fiber preform is 0.6g / cm 3 , the mass ratio of the tire mesh to the plain fabric in the middle layer is 2:8; Step 2: Preparation of hydroxy magnesium silicate: Take 4.5g magnesium oxide, 4.5g silicon dioxide, and 400mL distilled water, stir evenly, add 13mL of 1mol / L sodium hydroxide solution, heat to 200℃ and react for 11h, cool to 27℃, wash, dry, grind, and ball-mill to obtain hydroxy magnesium silicate; Step 3: Preparation of porous molybdenum disulfide: Take 1.2 g of ammonium heptamolybdate, 0.5 g of thiourea, and 60 mL of deionized water, ultrasonically treat for 8 min, react at 198 ° C for 23 h, cool, wash, and dry to obtain porous molybdenum disulfide; Step 4: Preparation of porous molybdenum disulfide-hydroxymagnesium silicate composite: 0.05 g of porous molybdenum disulfide, 0.6 g of magnesium hydroxysilicate, and 20 mL of a sodium alginate solution with a mass concentration of 1% were taken and ultrasonically dispersed to obtain a mixed solution A; 3 g of ferric chloride, 2 g of ferric chloride tetrahydrate, and 100 mL of deionized water were taken and stirred evenly, and then dropped into the mixed solution A, and the temperature was raised to 62° C., reacted for 45 min, freeze-dried, and ground to obtain a porous molybdenum disulfide-magnesium hydroxysilicate composite; Step 5: Preparation of phenolic resin A: Take 0.6 mL of ammonia water, 100 mL of deionized water, and 40 mL of ethanol, stir for 60-70 min, add 1 g of resorcinol and 1 mL of diethylenetriamine, stir for 35 min, dropwise add 1.5 mL of formaldehyde solution, continue stirring for 23 h, centrifuge, wash, and dry to obtain phenolic resin A; Step 6: Preparation of phenolic resin B: Phenolic resin A, ethanol, acetone, and hexamethylenetetramine are mixed in a weight ratio of 1:1:1:0.1 to obtain phenolic resin B; Step 7: Preparation of mixed slurry: Take 100g of phenolic resin B, 5g of silicon powder, 32g of ceramic powder SiC, and 2g of porous molybdenum disulfide-hydroxy magnesium silicate composite, add ammonia water and hydrochloric acid to adjust the pH value to 11, and ball mill for 47h to obtain a mixed slurry; Step 8: Preparation of carbon ceramic brake disc: The fiber preform is immersed in the mixed slurry under vacuum conditions for 12 minutes, taken out and dried, kept warm for 30 minutes at 150°C and 30MPa, thermally cracked at 1000°C, kept warm at 1800°C for 55 minutes, processed into the shape of a brake disc, and then siliconized in a vacuum furnace at an infiltration temperature of 1650°C and kept warm for 5 hours. Nitrogen is introduced to 0.1MPa at 1500°C, cooled and ground to obtain a carbon-ceramic brake disc.

[0022] Embodiment 2: A method for preparing a carbon ceramic brake disc, comprising the following steps: Step 1: Preparation of fiber preform: The plain cloth and the tire net are stacked in a cycle to obtain an intermediate layer; then the tire net with a thickness of 5 mm is laid flat on the upper and lower surfaces of the intermediate layer, and needle punching is performed to obtain a fiber preform; the needle punching density is 10 needles / cm 2 The volume density of the fiber preform is 0.6 g / cm 3 , the mass ratio of the tire mesh to the plain fabric in the middle layer is 2:8; Step 2: Preparation of hydroxy magnesium silicate: Take 4.5g magnesium oxide, 4.5g silicon dioxide, and 400mL distilled water, stir evenly, add 13mL of 1mol / L sodium hydroxide solution, heat to 200℃ and react for 10h, cool to 25℃, wash, dry, grind, and ball-mill to obtain magnesium hydroxysilicate; Step 3: Preparation of porous molybdenum disulfide: Take 1.2 g of ammonium heptamolybdate, 0.5 g of thiourea, and 60 mL of deionized water, ultrasonically treat for 5 min, react at 195 ° C for 22 h, cool, wash, and dry to obtain porous molybdenum disulfide; Step 4: Preparation of porous molybdenum disulfide-hydroxymagnesium silicate composite: 0.05 g of porous molybdenum disulfide, 0.6 g of magnesium hydroxysilicate, and 20 mL of a sodium alginate solution with a mass concentration of 1% were taken and ultrasonically dispersed to obtain a mixed solution A; 3 g of ferric chloride, 2 g of ferric chloride tetrahydrate, and 100 mL of deionized water were taken and stirred evenly, and then dropped into the mixed solution A, and the temperature was raised to 60°C, reacted for 40 minutes, freeze-dried, and ground to obtain a porous molybdenum disulfide-magnesium hydroxysilicate composite; Step 5: Preparation of phenolic resin A: Take 0.6 mL of ammonia water, 100 mL of deionized water, and 40 mL of ethanol, stir for 60 min, add 1 g of resorcinol and 1 mL of diethylenetriamine, stir for 30 min, dropwise add 1.5 mL of formaldehyde solution, continue stirring for 22 h, centrifuge, wash, and dry to obtain phenolic resin A; Step 6: Preparation of phenolic resin B: Phenolic resin A, ethanol, acetone, and hexamethylenetetramine are mixed in a weight ratio of 1:1:1:0.1 to obtain phenolic resin B; Step 7: Preparation of mixed slurry: Take 100g phenolic resin B, 5g silicon powder, 32g ceramic powder B 4 C. 2 g of porous molybdenum disulfide-hydroxymagnesium silicate composite was added with ammonia water and hydrochloric acid to adjust the pH value to 11, and ball milled for 46 h to obtain a mixed slurry; Step 8: Preparation of carbon ceramic brake disc: The fiber preform is immersed in the mixed slurry under vacuum conditions for 10 minutes, taken out and dried, kept warm for 30 minutes at 150°C and 30MPa, thermally cracked at 1000°C, kept warm at 1800°C for 50 minutes, processed into the shape of a brake disc, and then siliconized in a vacuum furnace at an infiltration temperature of 1650°C and kept warm for 5 hours. Nitrogen is introduced to 0.1MPa at 1300°C, cooled and ground to obtain a carbon-ceramic brake disc.

[0023] Embodiment 3: A method for preparing a carbon ceramic brake disc, comprising the following steps: Step 1: Preparation of fiber preform: The plain cloth and the tire net are stacked in a cycle to obtain an intermediate layer; then the tire net with a thickness of 5 mm is laid flat on the upper and lower surfaces of the intermediate layer, and needle punching is performed to obtain a fiber preform; the needle punching density is 10 needles / cm 2 The volume density of the fiber preform is 0.6g / cm 3 , the mass ratio of the tire mesh to the plain fabric in the middle layer is 2:8; Step 2: Preparation of hydroxy magnesium silicate: Take 4.5g magnesium oxide, 4.5g silicon dioxide, and 400mL distilled water, stir evenly, add 13mL of 1mol / L sodium hydroxide solution, heat to 200℃ and react for 12h, cool to 30℃, wash, dry, grind, and ball-mill to obtain magnesium hydroxysilicate; Step 3: Preparation of porous molybdenum disulfide: Take 1.2 g of ammonium heptamolybdate, 0.5 g of thiourea, and 60 mL of deionized water, ultrasonically treat for 10 min, react at 200 ° C for 24 h, cool, wash, and dry to obtain porous molybdenum disulfide; Step 4: Preparation of porous molybdenum disulfide-hydroxymagnesium silicate composite: 0.05 g of porous molybdenum disulfide, 0.6 g of magnesium hydroxysilicate, and 20 mL of a sodium alginate solution with a mass concentration of 1% were taken and ultrasonically dispersed to obtain a mixed solution A; 3 g of ferric chloride, 2 g of ferric chloride tetrahydrate, and 100 mL of deionized water were taken and stirred evenly, and then dropped into the mixed solution A, and the temperature was raised to 65°C, reacted for 50 min, freeze-dried, and ground to obtain a porous molybdenum disulfide-magnesium hydroxysilicate composite; Step 5: Preparation of phenolic resin A: Take 0.6 mL of ammonia water, 100 mL of deionized water, and 40 mL of ethanol, stir for 70 min, add 1 g of resorcinol and 1 mL of diethylenetriamine, stir for 40 min, dropwise add 1.5 mL of formaldehyde solution, continue stirring for 24 h, centrifuge, wash, and dry to obtain phenolic resin A; Step 6: Preparation of phenolic resin B: Phenolic resin A, ethanol, acetone, and hexamethylenetetramine are mixed in a weight ratio of 1:1:1:0.1 to obtain phenolic resin B; Step 7: Preparation of mixed slurry: Take 100g of phenolic resin B, 5g of silicon powder, 32g of ceramic powder BN, and 2g of porous molybdenum disulfide-hydroxy magnesium silicate composite, add ammonia water and hydrochloric acid to adjust the pH value to 11, and ball mill for 48h to obtain a mixed slurry; Step 8: Preparation of carbon ceramic brake disc: The fiber preform is immersed in the mixed slurry under vacuum conditions for 15 minutes, taken out and dried, kept warm for 30 minutes at 150°C and 30MPa, thermally cracked at 1100°C, kept warm at 1800°C for 60 minutes, processed into the shape of a brake disc, and then siliconized in a vacuum furnace at an infiltration temperature of 1650°C and kept warm for 5 hours. Nitrogen is introduced to 0.1MPa at 1600°C, cooled and ground to obtain a carbon-ceramic brake disc.

[0024] Comparative Example 1: No hydroxy magnesium silicate was added, and the rest was the same as Example 1: Step 1: Preparation of fiber preform: The plain cloth and the tire net are stacked in a cycle to obtain an intermediate layer; then the tire net with a thickness of 5 mm is laid flat on the upper and lower surfaces of the intermediate layer, and needle punching is performed to obtain a fiber preform; the needle punching density is 10 needles / cm 2 The volume density of the fiber preform is 0.6g / cm 3 , the mass ratio of the tire mesh to the plain fabric in the middle layer is 2:8; Step 2: Preparation of porous molybdenum disulfide: Take 1.2 g of ammonium heptamolybdate, 0.5 g of thiourea, and 60 mL of deionized water, ultrasonically treat for 8 min, react at 198 ° C for 23 h, cool, wash, and dry to obtain porous molybdenum disulfide; Step 3: Preparation of modified porous molybdenum disulfide: Take 0.05g of porous molybdenum disulfide and 20mL of sodium alginate solution with a mass concentration of 1%, and disperse by ultrasonic to obtain a mixed solution A; take 3g of ferric chloride, 2g of ferric chloride tetrahydrate, and 100mL of deionized water, stir evenly, drop into the mixed solution A, heat to 62°C, react for 45min, freeze-dry, and grind to obtain modified porous molybdenum disulfide; Step 4: Preparation of phenolic resin A: Take 0.6 mL of ammonia water, 100 mL of deionized water, and 40 mL of ethanol, stir for 60-70 min, add 1 g of resorcinol and 1 mL of diethylenetriamine, stir for 35 min, dropwise add 1.5 mL of formaldehyde solution, continue stirring for 23 h, centrifuge, wash, and dry to obtain phenolic resin A; Step 5: Preparation of phenolic resin B: Phenolic resin A, ethanol, acetone, and hexamethylenetetramine are mixed in a weight ratio of 1:1:1:0.1 to obtain phenolic resin B; Step 6: Preparation of mixed slurry: Take 100g of phenolic resin B, 5g of silicon powder, 32g of ceramic powder SiC, and 2g of modified porous molybdenum disulfide, add ammonia water and hydrochloric acid to adjust the pH value to 11, and ball mill for 47h to obtain a mixed slurry; Step 7: Preparation of carbon ceramic brake disc: The fiber preform is immersed in the mixed slurry under vacuum conditions for 12 minutes, taken out and dried, kept warm for 30 minutes at 150°C and 30MPa, thermally cracked at 1000°C, kept warm at 1800°C for 55 minutes, processed into the shape of a brake disc, and then siliconized in a vacuum furnace at an infiltration temperature of 1650°C and kept warm for 5 hours. Nitrogen is introduced to 0.1MPa at 1500°C, cooled and ground to obtain a carbon-ceramic brake disc.

[0025] Comparative Example 2: Fe3O4 is not loaded on the porous molybdenum disulfide-hydroxymagnesium silicate composite, and the rest is the same as Example 1: Step 1: Preparation of fiber preform: The plain cloth and the tire net are stacked in a cycle to obtain an intermediate layer; then the tire net with a thickness of 5 mm is laid flat on the upper and lower surfaces of the intermediate layer, and needle punching is performed to obtain a fiber preform; the needle punching density is 10 needles / cm 2 The volume density of the fiber preform is 0.6 g / cm 3 , the mass ratio of the tire mesh to the plain fabric in the middle layer is 2:8; Step 2: Preparation of hydroxy magnesium silicate: Take 4.5g magnesium oxide, 4.5g silicon dioxide, and 400mL distilled water, stir evenly, add 13mL of 1mol / L sodium hydroxide solution, heat to 200℃ and react for 11h, cool to 27℃, wash, dry, grind, and ball-mill to obtain hydroxy magnesium silicate; Step 3: Preparation of porous molybdenum disulfide: Take 1.2 g of ammonium heptamolybdate, 0.5 g of thiourea, and 60 mL of deionized water, ultrasonically treat for 8 min, react at 198 ° C for 23 h, cool, wash, and dry to obtain porous molybdenum disulfide; Step 4: Preparation of porous molybdenum disulfide-hydroxymagnesium silicate composite: 0.05 g of porous molybdenum disulfide, 0.6 g of magnesium hydroxysilicate, and 20 mL of a sodium alginate solution with a mass concentration of 1% were taken and ultrasonically dispersed to obtain a mixed solution A. 100 mL of deionized water was taken and dropped into the mixed solution A, and the temperature was raised to 62° C., reacted for 45 min, freeze-dried, and ground to obtain a porous molybdenum disulfide-magnesium hydroxysilicate composite. Step 5: Preparation of phenolic resin A: Take 0.6 mL of ammonia water, 100 mL of deionized water, and 40 mL of ethanol, stir for 60-70 min, add 1 g of resorcinol and 1 mL of diethylenetriamine, stir for 35 min, dropwise add 1.5 mL of formaldehyde solution, continue stirring for 23 h, centrifuge, wash, and dry to obtain phenolic resin A; Step 6: Preparation of phenolic resin B: Phenolic resin A, ethanol, acetone, and hexamethylenetetramine are mixed in a weight ratio of 1:1:1:0.1 to obtain phenolic resin B; Step 7: Preparation of mixed slurry: Take 100g of phenolic resin B, 5g of silicon powder, 32g of ceramic powder SiC, and 2g of porous molybdenum disulfide-hydroxy magnesium silicate composite, add ammonia water and hydrochloric acid to adjust the pH value to 11, and ball mill for 47h to obtain a mixed slurry; Step 8: Preparation of carbon ceramic brake disc: The fiber preform is immersed in the mixed slurry under vacuum conditions for 12 minutes, taken out and dried, kept warm for 30 minutes at 150°C and 30MPa, thermally cracked at 1000°C, kept warm at 1800°C for 55 minutes, processed into the shape of a brake disc, and then siliconized in a vacuum furnace at an infiltration temperature of 1650°C and kept warm for 5 hours. Nitrogen is introduced to 0.1MPa at 1500°C, cooled and ground to obtain a carbon-ceramic brake disc.

[0026] Comparative Example 3: The phenolic resin is not modified by using diethylenetriamine, and the rest is the same as Example 1: Step 1: Preparation of fiber preform: The plain cloth and the tire net are stacked in a cycle to obtain an intermediate layer; then the tire net with a thickness of 5 mm is laid flat on the upper and lower surfaces of the intermediate layer, and needle punching is performed to obtain a fiber preform; the needle punching density is 10 needles / cm 2 The volume density of the fiber preform is 0.6g / cm 3 , the mass ratio of the tire mesh to the plain fabric in the middle layer is 2:8; Step 2: Preparation of hydroxy magnesium silicate: Take 4.5g magnesium oxide, 4.5g silicon dioxide, and 400mL distilled water, stir evenly, add 13mL of 1mol / L sodium hydroxide solution, heat to 200℃ and react for 11h, cool to 27℃, wash, dry, grind, and ball-mill to obtain hydroxy magnesium silicate; Step 3: Preparation of porous molybdenum disulfide: Take 1.2 g of ammonium heptamolybdate, 0.5 g of thiourea, and 60 mL of deionized water, ultrasonically treat for 8 min, react at 198 ° C for 23 h, cool, wash, and dry to obtain porous molybdenum disulfide; Step 4: Preparation of porous molybdenum disulfide-hydroxymagnesium silicate composite: 0.05 g of porous molybdenum disulfide, 0.6 g of magnesium hydroxysilicate, and 20 mL of a sodium alginate solution with a mass concentration of 1% were taken and ultrasonically dispersed to obtain a mixed solution A; 3 g of ferric chloride, 2 g of ferric chloride tetrahydrate, and 100 mL of deionized water were taken and stirred evenly, and then dropped into the mixed solution A, and the temperature was raised to 62° C., reacted for 45 min, freeze-dried, and ground to obtain a porous molybdenum disulfide-magnesium hydroxysilicate composite; Step 5: Preparation of phenolic resin: Take 0.6 mL of ammonia water, 100 mL of deionized water, and 40 mL of ethanol, stir for 60-70 min, add 1 g of resorcinol, stir for 35 min, dropwise add 1.5 mL of formaldehyde solution, continue stirring for 23 h, centrifuge, wash, and dry to obtain phenolic resin; Step 6: Preparation of phenolic resin B: Phenolic resin, ethanol, acetone, and hexamethylenetetramine are mixed in a weight ratio of 1:1:1:0.1 to obtain phenolic resin B; Step 7: Preparation of mixed slurry: Take 100g of phenolic resin B, 5g of silicon powder, 32g of ceramic powder SiC, and 2g of porous molybdenum disulfide-hydroxy magnesium silicate composite, add ammonia water and hydrochloric acid to adjust the pH value to 11, and ball mill for 47h to obtain a mixed slurry; Step 8: Preparation of carbon ceramic brake disc: The fiber preform is immersed in the mixed slurry under vacuum conditions for 12 minutes, taken out and dried, kept warm for 30 minutes at 150°C and 30MPa, thermally cracked at 1000°C, kept warm at 1800°C for 55 minutes, processed into the shape of a brake disc, and then siliconized in a vacuum furnace at an infiltration temperature of 1650°C and kept warm for 5 hours. Nitrogen is introduced to 0.1MPa at 1500°C, cooled and ground to obtain a carbon-ceramic brake disc.

[0027] experiment: The carbon ceramic brake discs prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests. The shear strength of the carbon ceramic brake discs was tested with reference to GB / T40388-2021 carbon / carbon composite material shear strength, and the friction coefficient of the carbon ceramic brake discs was tested with reference to SAEJ2522-2003. The obtained data are shown in the following table: Conclusion: From the comparison of the data in the table, it can be seen that in Comparative Example 1, no hydroxy magnesium silicate is added, and the wear resistance and mechanical properties of the carbon ceramic brake disc are reduced. In Comparative Example 2, ferroferric oxide is not loaded on the porous molybdenum disulfide-hydroxy magnesium silicate composite, and the dispersion of the porous molybdenum disulfide-hydroxy magnesium silicate composite is poor, which affects the strength and wear resistance of the carbon ceramic brake disc. In Comparative Example 3, diethylenetriamine is not used to modify the phenolic resin, and the dispersion of the porous molybdenum disulfide-hydroxy magnesium silicate composite in the resin matrix is ​​poor, and the strength and wear resistance of the carbon ceramic brake disc are also reduced. In the embodiments 1 to 3 of the present invention, plain cloth is used to replace the non-woven cloth, which increases the strength of the structural part. On the other hand, the friction layer adopts a tire net, which solves the defect that the non-woven cloth on the friction surface is easy to fall off, and the tire net fiber content is greatly reduced, so that the ceramic content of the friction surface is increased, thereby improving the wear performance of the material. The present invention prepares a hydroxy magnesium silicate with excellent wear resistance, and then the hydroxy magnesium silicate is compounded with porous molybdenum disulfide. By adding ferric chloride and ferric chloride tetrahydrate, the porous molybdenum disulfide-hydroxy magnesium silicate composite is loaded with ferric oxide, which further improves the strength and wear resistance of the carbon ceramic brake disc. The present invention also uses diethylenetriamine to prepare a phenolic resin B. The addition of diethylenetriamine improves the chelating property of the phenolic resin B and the porous molybdenum disulfide-hydroxy magnesium silicate composite, thereby improving the dispersion performance of the porous molybdenum disulfide-hydroxy magnesium silicate composite, and improving the strength and wear resistance of the carbon ceramic brake disc.

[0028] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a carbon ceramic brake disc, characterized in that: The following steps are involved: Step 1: Take phenolic resin B, silicon powder, ceramic powder, porous molybdenum disulfide-hydroxy magnesium silicate composite, adjust the pH value to 11-12, and ball mill for 46-48 hours to obtain a mixed slurry; Step 2: stacking the plain cloth and the tire net in a circular manner to obtain an intermediate layer; then laying the tire net flat on the upper and lower surfaces of the intermediate layer, and needle punching to obtain a fiber preform; Step 3: Immerse the fiber preform in the mixed slurry for 10-15 minutes, take it out, dry it, keep it warm for 30-40 minutes at 150°C and 30MPa, thermally crack it at 1000-1100°C, keep it warm at 1800°C for 50-60 minutes, process it into the shape of a brake disc, and then siliconize it in a vacuum furnace, keep it warm, introduce nitrogen to 0.1MPa at 1300-1600°C, cool it, and grind it to obtain a carbon ceramic brake disc.

2. The method for preparing a carbon ceramic brake disc according to claim 1, characterized in that: The preparation method of the porous molybdenum disulfide-hydroxy magnesium silicate composite is as follows: taking porous molybdenum disulfide, hydroxy magnesium silicate and sodium alginate solution, ultrasonically dispersing to obtain a mixed solution A; taking ferric chloride, ferric chloride tetrahydrate and deionized water, stirring evenly, dropping into the mixed solution A, heating to 60-65° C., reacting for 40-50 minutes, freeze-drying and grinding to obtain the porous molybdenum disulfide-hydroxy magnesium silicate composite.

3. The method for preparing a carbon ceramic brake disc according to claim 2, characterized in that: The preparation method of the porous molybdenum disulfide is: taking ammonium heptamolybdate, thiourea and deionized water, ultrasonically treating for 5-10 minutes, reacting at 195-200° C. for 22-24 hours, cooling, washing and drying to obtain the porous molybdenum disulfide.

4. The method for preparing a carbon ceramic brake disc according to claim 2, characterized in that: The preparation method of the magnesium hydroxysilicate is as follows: taking magnesium oxide, silicon dioxide and distilled water, stirring evenly, adding sodium hydroxide solution, heating to 200° C. to react for 10-12 hours, cooling to 25-30° C., washing, drying, grinding and ball milling to obtain magnesium hydroxysilicate.

5. The method for preparing a carbon ceramic brake disc according to claim 1, characterized in that: The preparation method of the phenolic resin B is as follows: phenolic resin A, ethanol, acetone and hexamethylenetetramine are mixed evenly to obtain phenolic resin B.

6. The method for preparing a carbon ceramic brake disc according to claim 5, characterized in that: The preparation method of the phenolic resin A is as follows: taking ammonia water, deionized water and ethanol, stirring for 60-70 minutes, adding resorcinol and diethylenetriamine, stirring for 30-40 minutes, dropping formaldehyde solution, continuing stirring for 22-24 hours, centrifuging, washing and drying to obtain the phenolic resin A.

7. The method for preparing a carbon ceramic brake disc according to claim 5, characterized in that: The mass ratio of the phenolic resin A, ethanol, acetone and hexamethylenetetramine is 1:1:1:0.

1.

8. The method for preparing a carbon ceramic brake disc according to claim 1, characterized in that: The ceramic powder is any one of SiC, B4C and BN; the particle size of the ceramic powder is 0.5-5 μm.

9. A carbon-ceramic brake disc prepared according to the method for preparing a carbon-ceramic brake disc according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Manufacturing method for environment-friendly high-performance brake pad

    CN105546002A

  • Carbon-ceramic brake material preparation method and carbon-ceramic brake disc preparation method

    CN105565839A

  • Manufacturing method of brake pad for heavy machine

    CN105605131A

  • Method for preparing environmental-friendly brake pad with reclaimed materials

    CN105733176A

  • Preparation method of high-performance low-copper brake pad

    CN105754284A